Safety and efficacy of total colectomy with D3 lymph node dissection at colorectal cancer, developed at inflammatory bowel diseases (case control study) - P. V. Tsarkov; I. A. Tulina; S. K. Efetov; Yu. E. Kitsenko; D. N. Fedorov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To compare results of radical surgery in IBD-associated colorectal cancer (IBD-CRC) and sporadic colorectal cancer (spCRC) patients. Material and methods. The main group included retrospective cases of IBD-CRC with total colectomy and D3 lymph node (LN) dissection. The control group included matched cases of spCRC in 1:3 ratio according to localization and stage. Results. Overall 6 IBD-CRC and 18 spCRC patients were matched. IBD-CRC patients had longer operation time (313±37 vs 240±16 min, p=0.05), while there was no significant difference in mean volume of blood loss and postoperative stay duration (383±145 and 186±29 ml, p=0.24; 15.7±3.2 and 14.1±0.9 days, p=0.5 respectively). IBD-CRC patients spent longer time in ICU than spCRC (2.3±0.6 and 1.17±0.2 days, p=0.02) and had later bowel peristalsis restoration (2.0±0.4 and 1.3±0.1 days, p=0.02), however, time to first gas and stool discharge via stoma didn’t differ (2.5±1.4 and 2.1±0.6 days, p=0.5; 4.2±3.4 and 2.4±0.7 days, p=0.3). Tumor grade, histological type and adenoma rate didn’t differ between groups. Average number of involved LN in IBDCRC and spCRC was 39±16 and 30±5 (p=0.6). The rate of metastatic LN was 33.3% in both groups. The mean follow-up time was 27.3±5.3 months. Distant metastases were detected in 33.3% and 16.7% of IBD-CRC and spCRC cases respectively (p=0.4), without local recurrence in both groups. Conclusion. Tumor and LN characteristics in spCRC and IBD-CRC were similar, therefore radical surgery with extended LN dissection is recommended for IBDCRC patients.